Effects of Diutina rugosa SD-17 on growth performance, intestine morphology, and immune status of chickens. (27th July 2019) - Wang, J; Wang, B; Du, H; Zhang, H; Li, H; Wang, F; Zhao, X
Abstract: Probiotics are considered the preferred alternatives to antibiotics for growth promotion and disease prevention. Previous studies have confirmed that Diutina rugosa SD-17 has the potential as a probiotic. We evaluated the probiotic effect of D. rugosa SD-17 on 360 one-day-old Hy-line brown chickens that were divided into 2 groups, and each group contained 6 replicate pens with 30 birds per pen. The chickens were fed with basal diet supplemented with or without D. rugosa SD-17, and the effects of D. rugosa SD-17 on growth performance, intestine morphology, and immune status were assessed. Body weight was significantly improved from week 3 to 6 ( P < 0.05), and the feed conversion ratio was significantly improved in weeks 1 and 2 ( P < 0.001). The length of the duodenum was lengthened significantly in week 3 ( P < 0.05), and supplementation of D. rugosa SD-17 significantly increased villus height and villus height to crypt depth ratio in the ileum in week 3 ( P < 0.05). Expressions of tight-junction-related genes of zonula occludens-2 and occludin in the ileum were significantly increased ( P < 0.05). The proliferation capacity of blood lymphocytes stimulated by concanavalin A was significantly enhanced ( P < 0.05), and the proportion of helper T (Th ) cells increased significantly ( P < 0.05). Expressions of Th1 cell markers IL-2 and interferon (IFN)-γ and immune-related genes of IL-1β, transforming growth factor-β, and IFN-γ in ileum were significantly increased ( P < 0.05). These results indicated that D. rugosa SD-17 improved the growth and regulated immunity of chickens, and could be optimized for use as a feed additive for livestock and poultry.